Marketing Structure and the Theory of Economic Interdependence: Early Analytical Developments - Dixon, Donald F. (Journal of Macromarketing, 1991)
The elements of an economic system are interdependent, and the structure formed by system interrelationships is crucial to the survival of an economy. Attempts to identify and measure structure are traced from the mid-eighteenth century to the publication of Distribution in a High-Level Economy The first major study including the marketing sector of an economy, Does Distribution Cost Too Much?, does not provide structural inferences because parts of the economic system were omitted, and system inputs were not specified. The often repeated estimate that marketing costs represent 59% of the consumer's dollar is overstated because system output is underestimated. Structural inferences can be developed with data presented in Distribution in a High-Level Economy, using the analytical framework provided by the Leontief input-output table.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjc2MTQ2NzkxMDExMDAyMDI